Taxonomic status of Chrysophanus phoenicurus transcaucasicus Miller, 1923 (Lepidoptera, Lycaenidae), with the designation of a neotype - Krupitsky, Anatoly V. (Zootaxa, 2017)
The taxonomic status is clarified for the lycaenine taxon Chrysophanus phoenicurus transcaucasicus Miller, 1923 described from one male collected in eastern Turkey and currently treated within the genus Athamanthia Zhdanko, 1983. Based on the appearance and morphology of the male genitalia compared with A. phoenicurus (Lederer, 1870), it is recognized here as a separate species, A. transcaucasica (Miller, 1923), stat. nov. (= Lycaena melicertes Nekrutenko, 1985). Its holotype is lost, and a neotype is designated herein from recent material collected near the type locality to retain nomenclatural stability. A key to the species of the A. phoenicurus group based on wings pattern and male genitalia is presented.